DWT 2019
DOI: 10.5004/dwt.2019.23935
|View full text |Cite
|
Sign up to set email alerts
|

Removal of chromium (III) from tannery wastewater by electrochemical peroxidation process in a bench scale reactor

Abstract: Chromium(III) used in tanning process is not consumed fully and around 30-40% of Chromium(III) is washed away to the environment causing severe environmental problem especially to the aquatic system. To remove Chromium(III) from wastewater, many different treatment techniques have been developed. This study deals with the ability of electrochemical peroxidation process for the removal of Chromium(III) from tannery wastewater in a batch stirred tank bench scale reactor with hopper bottom of 5 L working volume e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The results are shown in Figure 8. Compared to synthetic wastewater, real wastewater requires a higher concentration of Fe 2þ to start the Fenton reaction, which will damage large molecules (Selvabharathi et al 2019). If the concentration is kept low, adding ferrous salts to achieve metal coagulation may be enough to entirely remove the organic contaminants.…”
Section: Interactive Effect Of Spiked Fe 2þ On Cod Removalmentioning
confidence: 99%
“…The results are shown in Figure 8. Compared to synthetic wastewater, real wastewater requires a higher concentration of Fe 2þ to start the Fenton reaction, which will damage large molecules (Selvabharathi et al 2019). If the concentration is kept low, adding ferrous salts to achieve metal coagulation may be enough to entirely remove the organic contaminants.…”
Section: Interactive Effect Of Spiked Fe 2þ On Cod Removalmentioning
confidence: 99%
“…The electrochemical peroxidation process has a similar mechanism to electrocoagulation, but better COD removal results were obtained with the addition of H2O2 [12][13][14]. Several studies have reported that COD of coke wastewater can be removed up to 90 % by electrochemical peroxidation, whereas by electrocoagulation, up to 30 % was removed only [13].…”
Section: Introductionmentioning
confidence: 99%
“…There is inhibition of biological degradation due to chromium content and sulphide ions indicating the antibacterial activity. Conventional methods used for wastewater treatment are expensive and are not eco-friendly besides requiring high energy and large quantities of chemicals [6]. The increasing demand for eco-friendly technologies has forced researchers, scientists and leather industries to search for cost-effective alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in Eqs. ( 4) and (5), this is not quite feasible in the oxidation phase that leads to quantification of H 2 O 2 and Fe 2+ [6]. According to Eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation